Strategi Guru Pendidikan Agama Katolik dalam Meningkatkan Keterampilan 4Cs Siswa Kelas XI - Sihotang, Din Oloan; Lumbanbatu, Johannes Sohirimon; Tarigan, Fransiskus (STIPAS Keuskupan Agung Kupang, 2025)
This study aims to explore the teaching strategies implemented by Catholic Religious Education (CRE) teachers in developing 21st-century skills, namely Critical Thinking, Creativity, Collaboration, and Communication (4Cs), at SMAS Katolik Tri Sakti Medan. Using a qualitative approach and descriptive method, this research analyzes how teachers apply teaching methods that encourage active student participation through group discussions, case study-based projects, and the use of visual media. The findings show that the application of teaching strategies based on Piaget’s constructivist theory and Mayer’s multimodal theory successfully creates a dynamic and interactive learning environment. Teachers provide space for students to ask questions, engage in discussions, and critically analyze the material, which supports the development of 4Cs skills. Students’ critical thinking, communication, creativity, and collaboration skills significantly improved through project-based and collaborative learning. Overall, these findings emphasize the importance of innovative and varied teaching approaches in preparing students for the challenges of the 21st century, while maintaining the moral and spiritual values in religious education.